Pengaruh budaya organisasi, reward, dan kepemimpinan transformasional terhadap turnover intention dengan kepuasan kerja sebagai variabel mediasi pada karyawan bank swasta di Jakarta - Siahaan, Sarah Septira; Firdausy, Carunia Mulya (Jurnal Manajemen Bisnis dan Kewirausahaan, 2025)
This study analyzes the influence of organizational culture, rewards, and transformational leadership on turnover intention, with job satisfaction as a mediating variable, using PLS-SEM on 246 employees of private banks in Jakarta. The results show that all three factors significantly increase both job satisfaction and turnover intention, while job satisfaction does not significantly affect turnover intention and fails to mediate any of the relationships. The novelty of this research lies in examining these three key organizational factors within a single mediation model in the context of Indonesia’s private banking sector, which remains underexplored. The unexpected positive effects on turnover intention reveal contextual dynamics not fully aligned with Social Exchange Theory (SET). This study contributes by highlighting that improvements in culture, rewards, or leadership alone are insufficient to reduce turnover intention without addressing deeper issues such as job pressure, unmet expectations, and perceived inequity. These insights guide organizations in designing more targeted retention strategies.